E-Commerce as Mechanism for Enhancing Micro and Small Enterprises: The Case of a Port Conurbated Area in the Southeast of Mexico (European Journal of Marketing and Economics, 2025)
E-commerce arised from the greater demand  experienced by companies and the need of their administration to make better use of information technology and to find a better way to adapt the new technologies, in order to improve the relationship between customer and supplier. In this scenario, from micro to large interprises could benefit by developing e-commerce strategies; in the mexican context, micro, small and médium enterprises represent more tan 90% of business units but show low preference for adopting e-commerce strategies. Based on the above, this study aims to detect which elements appart small enterprises from e-commerce. After applying a survey among 100 small enterprises, it was observed that the most important barriers were the high cost of implementation, lack of qualified personnel and lack of information.
Keywords: e-commerce; micro enterprises; mexican SMEs.